A study on level of public awareness of takaful insurance in Malaysia / Nor Hazirah Ab Kadir and Nur Hazwani Abdul Rahman - Ab Kadir, Nor Hazirah; Abdul Rahman, Nur Hazwani (Faculty of Business and Management, 2013)
The scope of study in this research is focuses on level of public awareness of takaful insurance. The study coverage was focused only in Bangsar as it is located in an urban area. In 2005, Bangsar's population stood at some 40,000people based on the malaysiafactbook.com/Bangsar. 120 respondents are taken from the population to be as sample. The time frame of this study is five working days and in 5 months from 28 January 2013 until 14 June 2013.